Transradial Approach for Percutaneous Interventions - Zhou, Yujie; Kiemeneij, Ferdinand; Saito, Shigeru; Liu, Wei (Springer Netherlands : Imprint: Springer, 2017)
This book outlines the state of the art in transradial intervention and illustrates case-based learning for the transradial access (TR access) technique, especially in complex lesions. Offering a practical guide, it includes essential tips and tricks on how to overcome anatomical complexities, how to avoid radial complications, multiple case-based learning for very complex PCI, etc. It also discusses the advantages of the TR intervention, such as reduced vascular access site complications and immediate patient mobilization. The authors, who work at respected transradial centers, share their extensive experience with TR intervention, providing a comprehensive review of current percutaneous interventions for cardiac surgeons and cardiothoracic surgical residents. Editor Yujie Zhou is a Professor at the department of Cardiology, Anzhen Hospital, Beijing, China. Editor Wei Liu is a physician at the same department. Editor Ferdinand Kiemeneij is is interventional cardiologist at Department of Cardiology, Tergooi Hospital, Blaricum, the Netherlands. Editor Shigeru Saito, FACC, FSCAI, FJCC, is the director of cardiology and Catheterization Laboratories, Shonan Kamakura General Hospital, Kamakura, Japan.
Keywords: Medicine.; Angiology.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books